(3GdaVd GdeRjO Ydi HZjI GdeSJajOs - (3hLjg GdOjf YHO GdQMef Hf Ydj Hf eMeO Hf YeQ GdTjHGfi GdTGaYjs; (3GHf GdOjHY , YHO GdQMef Hf Ydj Hf eMeO GdTjHGfj GdRHjOj, hLjg GdOjf,J (B944 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd ddPjf CMSfh GdMSfi s
(3BNQgG (B:s
(3hgPG BNQ eG bUOJg ef LeY gPG GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B159s
Keywords: (3GdJGQjNs